HAKIKAT MANUSIA DALAM PERSPEKTIF AL-QUR’AN - Elizabeth Kristi; Alwizar Alwizar; Kadar Yusuf (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2022)
Abstract This paper aims to find out the nature of humans on this earth in the perspective of the Qur'an. Humans are creatures who have different minds and thoughts from animals and other God's creations. Humans are always looking for ways to continue to live, carry out all activities to always meet all their needs. In order not to get carried away with the life of the world, humans must know the essence of existence, for what they were created. The method in this research is a library research method or library research by collecting data through scientific literature. In the Qur'an there are words that express the meaning of humans including, al-Insan, al-Ins, al-Nas, al-Basyar, and Bani Adam. Each of these words is different from each other in its use and meaning in the verses of the Qur'an. The functions and roles of humans according to the Qur'an are twofold, namely, as servants of Allah and as caliphs. When humans understand the function and role as 'abdullah and caliph, then some human tasks on earth must be carried out. These tasks include, seeking knowledge, prospering the earth, maintaining trust, and working according to their respective fields. So when humans know their obligations according to what Allah says in the Qur'an, humans will realize and fulfill these obligations according to the nature of being on Allah's earth. Keywords: Human, substance, al-Qur’an